(untitled) (Journal of Medicine, 2014)
Chicken pox is a self-limiting, infectious disease caused by Varicella-zoster virus (VZV). In adults though rare, severe form of disease may cause complications like hepatitis, pneumonia, encephalitis. We present here a case of young male with life threatening complications of chicken pox who survived due to prompt & timely management. DOI: http://dx.doi.org/10.3329/jom.v15i1.19873 J Medicine 2014; 15: 55-57